Long term survival of patients mobilised early after acute myocardial infarction. - West, R R (1985)
A Welsh multicentre trial of early (fifth day) compared with late (tenth day) mobilisation in 742 patients after uncomplicated myocardial infarction, reported previously, found that there were no significant differences in survival during the first year, but a partial follow up beyond the first year survival showed a significantly reduced survival during the second and third years among patients mobilised early. A full 10 year follow up of all patients admitted to the trial was therefore carried out. A small difference in survival was confirmed, which reached about 5% at four years; but the difference was not statistically significant. Further analysis suggested the possibility of real differences in survival in certain subgroups, but the present evidence was not sufficient to provide contraindication to mobilisation five days after uncomplicated myocardial infarction.